2021
DOI: 10.1097/txd.0000000000001141
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Perfusion With Methylprednisolone Attenuates Brain Death-induced Lung Injury in Rats

Abstract: Background. The onset of brain death (BD) leads to the deterioration of potential donor lungs. Methylprednisolone is considered to increase lung oxygenation capacity and enhance the procurement yield of donor lungs, when applied in situ, during donor management. However, whether BD-induced lung damage is ameliorated upon treatment with methylprednisolone during acellular ex vivo lung perfusion (EVLP), remains unknown. We aimed to investigate whether the quality of lungs from brain-dead donors improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…These observations are consistent with previous data from Ohsumi et al, 19 who performed a detailed evaluation of rat lung damage and dysfunction during 4 h EVLP, after preservation with CI times (CITs) ranging from 20 min to 24 h. Lungs preserved up to a CIT of 12 h did not display significant alterations during EVLP, those with a CIT of 18 h disclosed reduction of compliance and increased release of lactate and apoptotic changes, and lungs with a CIT of 24 h immediately deteriorated. The authors concluded that a CIT of 18 h may be the limit for ischemic injury in this rat model of EVLP and would therefore be best suited to evaluate therapeutic interventions to treat damaged donor lungs; however, this conclusion seems different when rat lungs are obtained from brain dead, instead of euthanized, animals, as recently shown by van Zanden et al These authors indeed reported significant lung injury and dysfunction during EVLP of lungs procured after 3 h brain death and preserved for CIT of only 1 h. 20 , 21 …”
Section: Discussionmentioning
confidence: 73%
“…These observations are consistent with previous data from Ohsumi et al, 19 who performed a detailed evaluation of rat lung damage and dysfunction during 4 h EVLP, after preservation with CI times (CITs) ranging from 20 min to 24 h. Lungs preserved up to a CIT of 12 h did not display significant alterations during EVLP, those with a CIT of 18 h disclosed reduction of compliance and increased release of lactate and apoptotic changes, and lungs with a CIT of 24 h immediately deteriorated. The authors concluded that a CIT of 18 h may be the limit for ischemic injury in this rat model of EVLP and would therefore be best suited to evaluate therapeutic interventions to treat damaged donor lungs; however, this conclusion seems different when rat lungs are obtained from brain dead, instead of euthanized, animals, as recently shown by van Zanden et al These authors indeed reported significant lung injury and dysfunction during EVLP of lungs procured after 3 h brain death and preserved for CIT of only 1 h. 20 , 21 …”
Section: Discussionmentioning
confidence: 73%
“…Isolated treatments with cyclosporine and methylprednisolone have demonstrated benefits for physiological parameters and gas exchange during early graft function in preclinical models. Furthermore, therapies using modified adenovirus or lentivirus-based vectors during EVLP can deliver gene therapy directly to the organ, potentially reducing proinflammatory signaling without affecting other organ systems in the recipient [50][51][52][53].…”
Section: Allograft Function Optimizationmentioning
confidence: 99%
“…The main reason for this intervention has been the attempt to attenuate/prevent the deleterious effect of IRI and related inflammation and oxidative stress that donated organs are subjected to due to ischemia and other stresses occurring during the process of donation and organ procurement. In a rat model of brain death and ESLP, Van Zanden et al showed that the addition of methylprednisolone to the perfusate led to lower expression of IL-6 and IL-1b genes in the tissue, and lower perfusate IL-6 and improved positive inspiratory pressures compared to controls (189). In a study by Martens et al administration of methylprednisolone both before the arrest, and during the ESLP in a DCD porcine model led to a significant reduction in IL-1b, IL-8, and TNF-a, together with superior pulmonary compliance in treated lungs compared to the controls.…”
Section: Corticosteroidsmentioning
confidence: 99%